Significant Relationship between Hypertension and Obesity among Female Patients at A Hospital in Kupang, Indonesia - Wijaya, Darlene Monica; Indriarini, Desi; Wungouw, Herman Pieter Louis; Artawan, I Made (Althea Medical Journal, 2024)
Background: Hypertension or high blood pressure is one of the most common non-communicable diseases found nowadays, affecting 1.28 billion people worldwide and causing about 7.5 million deaths annually. Many factors contribute to hypertension, one of which is obesity. This study aimed to explore further the relationship between hypertension and obesity, especially in female patients in Kupang, Indonesia.Methods: This study was an analytical observational with a cross-sectional approach, including female patients visited the outpatient’s clinic of internal medicine at a hospital in Kupang, Indonesia from July to August 2022. A purposive sampling technique was used. Data collection used an aneroid sphygmomanometer, stethoscope, and health scale. Data analysis was performed using the Chi-Square test. The strength of the correlation was tested with the coefficient of contingency.Results: Of the 100 female patients, 28% had hypertension and 41% were obese. The majority were housewives, aged 46–66 years. Chi square test results showed a significant relationship between obesity and hypertension (p=0.006). However, the correlation test with the contingency coefficient showed a positive correlation with weak correlation (r = 0.283).Conclusions: There is a relationship between hypertension and obesity in female patients at a hospital in Kupang, Indonesia. This finding highlights the need for effective management and prevention strategies, as well as promoting healthy lifestyles.